Anti-Cancerous Potential of Polysaccharide Fractions Extracted from Peony Seed Dreg on Various Human Cancer Cell Lines Via Cell Cycle Arrest and Apoptosis - Zhang, Fang; Shi, Jun-Jun; Thakur, Kiran; Hu, Fei; Zhang, Jian-Guo; Wei, Zhao-Jun (Frontiers in Pharmacology, 2017)
In this study, four homo/heterogenous polysaccharides (HBSS, CHSS, DASS and CASS) extracted from peony seed dreg with respective molecular weights of 3467, 4677, 229 and 56 kDa were evaluated for anti-cancerous attributes in prostate cancer cells (Pc-3), colon cancer cells (HCT-116), human breast cancer cells (MCF-7), cervical cancer (Hela cells) and human embryonic kidney 293 (HEK 293) cells as control. Among them, CASS and DASS extracted by alkali, consisted of 34.43% Gal, 26.39% Ara, 21.80% Glc and 35.77% Ara, 19.35% Gal, 17.77% Man, respectively. CASS fraction had the most significant inhibitory effects on all the cell lines used whereas HBSS had least effect. The CASS shown remarkable inhibition and cytotoxic effects in Hela cells followed by other cell lines as compared to 5-fluorouracil (5-FU). CASS arrested cell cycle in G0/G1 phase except MCF-7 cells and increased apoptotic cells percentage varied in different treated cells. CASS down regulated the expression of Cyclin A/B1/D1/E1, CDK-1/2/4/6 and p15/16/21/27 excluding p53. The notable change in expression of proteins (Cytochrome C, Bax, Bcl-2, p-Caspase-3, -8, -9 and PARP) was observed followed by Apaf-1 and Survivin. These findings indicated that CASS has an anti-cancerous potential in the treatment of human cancers which make it a potent candidate in functional foods.